Working Time in Comparative Perspective, Volume Ii. Life-Cycle Working Time and Nonstandard Work - Tremblay, Diane-Gabrielle (Relations Industrielles / Industrial Relations, 2002)
The article reviews the book, "Working time in comparative perspective, v. 2," edited by Susan Houseman and Alice Nakamura.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Flexible hours; Labor Unions; Nontraditional careers; Work & family; Working hours